An Information Model for Asset Management in Higher Education Institutions in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
The research aim were to develop and to evaluate an information system model for asset management for higher education institution in thai supply chain . The samples are ten experts in the field of information system and supply chain. The data is analysed by means and standardized deviations. The research result shows that the model consists of four elements namely main components, Suppliers, Manufacturer, Customers, The result shows the overall rating mean of 3.65 and standard deviation of 0.66, which means that an information system model for asset management for higher education institution in thai supply chain is appropriate at the high level.The model can develop an information system .